Development of a Web-Based Information System Integrated with Artificial Intelligence and Gamification of the Jokotole Folklore to Strengthen Character Education and Multiliteracy of Junior High School Students in Madura - Dellia, Prita; Sudarto, Yoharwan Dwi; Amil, Ahmad Jami'ul; Mahendra, Yudha Dwi; Hasan, Muhammad Akmal; Jin, Xie (Universitas Trunojoyo Madura, 2025)
Literacy and character education in schools still often use conventional methods that are less appealing to students and do not utilize technology relevant to the local culture. This problem causes students to have low motivation to learn and difficulty understanding material based on folklore. This study aims to develop a Web-Based Information System Integrated with Artificial Intelligence and Gamification of the Jokotole Folklore as an interactive learning medium that is appropriate to the cultural context of Madura. The research method used a waterfall model that included needs analysis, system design, implementation, testing, and maintenance. The resulting product was the